PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 30 PEKANBARU - Andarini, Marissa; Witri, Gustimal; Putra, M. Jaya Adi (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
The background of this research is that there are several symptoms in the process of learning mathematics, namely: 1) passive / inactive students are characterized by the absence of questions after the teacher explains. 2) the number of noisy students is seen from the number of students who walk to see the assignment exercises given by the teacher. 3) the number of students who do not understand and understand is seen from the number of students who repeatedly ask when given practice. This research is a classroom action research that aims to improve student mathematics learning outcomes by applying problem-based learning models. This research was conducted in class V SDN 30 Pekanbaru. Data collection instruments in this thesis are teacher and student activity sheets and student learning outcomes assessment sheets. This thesis presents preliminary data before applying the problem-based learning model (PBM) which is 79.17 and increased to 83.04 in the first cycle and increased again to 92.60. Teacher activity also increased at each meeting, namely 65% with a good category in the first cycle the first meeting increased to 70% with a good category. In the second cycle also increased to 90% with a very good category at the first meeting and increased to 95% with a very good category at the second meeting. In the results of this study student learning outcomes have increased after applying the problem-based learning model (PBM) marked by an increase in teacher and student activities in each cycle. The results of this study prove that the problem-based learning model can improve mathematics learning outcomes of fifth grade students of SDN 30 Pekanbaru.